On Tesla: balancing sustainable car connectivity, silent lethality and luxury surveillance - Eski, Yarin (Criminological encounters, 2022)
This article analyses the increasingly influential role of tech companies in designing and deploying smart surveillancein private vehicles. Using the case of Tesla, a company that makes optimistic promises and has a hopeful vision for moresustainable electric cars by decreasing the ecological footprint, the article will discuss the problematic aspects of artificialintelligence, big data and algorithms for total surveillance by private companies. In particular, light will be shed on theissue of discourses on sustainable and smart vehicles that dim the light on the problematic aspects of luxury surveillance.As will be made clear, Tesla’s green and lean - aspirational - ambitions through different technological and surveillanceadvancements revive old forms of control and introduce a new set of power/knowledge relations. Beyond the questionof privacy and personal data harvesting, this article discusses the wider social and political consequences of smart carluxury surveillance by private companies such as Tesla.